Explaining the predictions of a boosted tree algorithm : application to credit scoring - Salvaire, Pierre Antony Jean Marie (2019)
Dissertation report presented as partial requirement for obtaining the Master’s degree in Information Management, with a specialization in Business Intelligence and Knowledge Management